2021
DOI: 10.1111/ecot.12309
|View full text |Cite
|
Sign up to set email alerts
|

Economic complexity, scientific productivity and income inequality in developing economies

Abstract: The state of income distribution in developing countries is important from an economic perspective, including per capita income, national savings, society's welfare and a sociopolitical perspective for governments to attract public voters.Therefore, economic justice has always been a concern of governments because of its undeniable economic and social consequences. The purpose of this study was to examine the impact of macroeconomic variables such as economic complexity, scientific productivity and various eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…(2017), Siddiq (2020), Chu and Hoang (2020), Sepehrdoust et al. (2021)). Thus, the findings of this study, along with the evidence from Bandeira Morais et al.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…(2017), Siddiq (2020), Chu and Hoang (2020), Sepehrdoust et al. (2021)). Thus, the findings of this study, along with the evidence from Bandeira Morais et al.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, Chu and Hoang (2020) and Sepehrdoust et al. (2021) found an increasing effect of economic complexity on income inequality.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The research by Sepehrdoust, et al (2021) examined the effect of macroeconomic variables on income inequality in developing countries from the period 2000 to 2019. They applied the panel-VAR model and found that income inequality decreases with an increase in economic complexity above a certain threshold.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In other words, because countries with higher economic complexity are likely to use newer techniques and methods in manufacturing products, we expect emissions of environmental pollutants to decrease in this group of countries. 20 …”
Section: Introductionmentioning
confidence: 99%